Comparison of different methods for image lag investigation of indirect converting flat-panel detectors - Hofmann, Th.; Burtzlaff, S.; Voland, V.; Salamon, M.; Nachtrab, Frank; Sukowski, F.; Uhlmann, N. (Nuclear Instruments and Methods in Physics Research Section A: Accelerators, Spectrometers, Detectors and Associated Equipment, 2009)
To measure the origins and dependencies of image lag in indirect converting flat-panel detectors, different methods were implemented. According to ASTM E 2597-07, the detector will be irradiated for a defined period with a constant flux. Then shutting off the tube, one can determine the image lag by monitoring the detector signal. We developed a different method, using a triggered shutter, to enable exactly defined illumination of the detector. Integration times longer than 1 s allow an exposure only during the delay time of the detector. This way, comparable results for image lag for decreasing intensity can be obtained. To investigate the image lag for increasing intensity, the triggered shutter stays open. By opening the shutter for more than one frame, then closing, it is possible to observe the build-up and decay of the image lag in dependence on the illumination time. Using these methods image lag was investigated with respect to irradiation intensity, time, incident X-ray spectrum, gain capacity of the detector and lag homogeneity of the detector surface.
EAM Import::2019-03-13